Dinâmica espacial das áreas úmidas e lagoas temporárias da Estação Ecológica de Itirapina - Ferreira, Guilherme Whyte Afonso [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Based on the variety of features of the Cerrado biome encountered at the study site, including the presence of wetlands (AUs) and seasonal occurrence of Temporary Ponds (LTs), it's easy to affirm that the study area has an enormous environmental relevance. Environments such as found in the Ecological Station of Itirapina (EEcl) are increasingly scarce in Brazil, especially in the Southeast. Those have been taken over by farming and livestock monocultures without the government objecting until 2012 with the New Forest Code, thus devastating most of the region's natural landscapes. Considering it is classified as a Conservation Unit in the National System of Conservation Units (SNUC), the studied fragment is protected by law, but still suffers impacts from the anthropic action in its surroundings. The present work aimed to evaluate and understand the spatial dynamics of the AUs and TLs of Itirapina Ecological Station through the manual delimitation of LTs and the application of NDVI vegetation index (Normalized Difference Vegetation Index) to evidence the variations in the AUs. Images used were collected from the United States Geological Survey (USGS), TM (1985-2011), ETM + (2012-2015) and OLI (2016-2017) provided by Landsat series with spatial resolution of 30m. For this to be done, literature was consulted regarding: geology and hydrology of the region, aspects of Brazilian legislation regarding the preservation of Cerrado and AUs, remote sensoring, precipitação data analysis, Brazilian Cerrado, climatic influences in the Southeast. Results indicated a close relationship between the total precipitation obtained during the rainy season (November to March) and the manifestation of the temporary ponds. This relationship is directly proportional, the more precipitated water in the rainy season, the larger the LT area. In addition, the occurrence of weather phenomenons El Niño and La Niña explain, respectively, most of the rise and fall in the...

Baseado na variedade de feições do bioma Cerrado encontrados no sítio de estudo, incluindo a presença de Áreas Úmidas (AUs) e ocorrência sazonal de Lagoas Temporárias (LTs), é fácil afirmar que a área de estudo tem enorme relevância ambiental. Ambientes como o encontrado na Estação Ecológica de Itirapina (EEcl) são cada vez mais escassos no Brasil, principalmente no Sudeste. Há muito foram invadidos por monoculturas agropecuárias, sem que houvesse objeção do governo até 2012 com o Novo Código Florestal, devastando assim a maioria das paisagens naturais da região. Por estar enquadrada como uma Unidade de Conservação no SNUC, o fragmento estudado está protegido por lei, mas ainda sofre impactos provenientes da ação antrópica em seu redor. O presente trabalho visou avaliar e compreender a dinâmica espacial das AUs e LTs da Estação Ecológica de Itirapina através da delimitação manual das LTs e da aplicação do índice de vegetação NDVI (Índice de Vegetação da Diferença Normalizada) para evidenciar as variações nas AUs. Imagens utilizadas foram retiradas do Serviço Geológico dos Estados Unidos (USGS), sendo essas dos sensores TM (1985-2011), ETM+ (2012-2015) e OLI (2016-2017) gerados pela série Landsat com resolução espacial de 30 m. Para isso, foram consultadas a literatura em relação à: geologia e hidrologia da região, os aspectos da legislação brasileira quanto à preservação do Cerrado e das AUs, sensoriamento remoto, análise de dados pluviométricos, Cerrado brasileiro e influências climáticas no Sudeste. Os resultados indicaram uma estreita relação, entre a pluviometria total obtida na estação chuvosa (novembro a março) e a manifestação das lagoas temporárias. Tal relação é diretamente proporcional: quanto mais água precipitada na estação chuvosa, maior a área das LTs. Além disso, a ocorrência dos fenômenos climáticos de El Niño e La Niña explicam, respectivamente...
Keywords: Lagoas; Sensoriamento remoto; Cerrados; Unidades de conservação; Impacto ambiental; Landsat (Satelites); Climatologia; Índice de Vegetação por Diferença Normalizada; Geoprocessamento; Itirapina (SP); Brasil